A method for transforming 2D imaging features with the AFSS‐loaded rotating Luneberg lens reflector. Issue 14 (20th September 2022) - Xu, Yong; Feng, Dejun; Wang, Junjie; Sui, Ran
Abstract: The micro‐motion target can perform micro‐Doppler modulation on the electromagnetic wave due to motion components in different directions, leading to the defocus effect of the target imaging feature along the azimuth direction. This phenomenon has been widely concerned and investigated in the field of target recognition and anti‐recognition. However, the micro‐motion target fails to transform image features along the distance direction according to its slow mechanical modulation speed. In comparison, electromagnetic metasurfaces can flexibly control the characteristics of electromagnetic waves with faster modulation speed through electronic control. It can realize the image feature transformation along the range direction. Inspired by this idea, a joint modulation method of rotational micro‐motion and electronic control through an active frequency selective surface (AFSS)‐loaded rotating Luneberg lens reflector is proposed. The signal models of micro‐motion modulation and non‐periodic AFSS modulation are established separately. On this basis, the imaging properties of the joint modulation are further analysed and the two‐dimensional (2D) defocusing phenomenon of the image is discovered. Moreover, the simulation of the measured synthetic aperture radar (SAR) data with different modulation methods is conducted to demonstrate the effectiveness of the proposed method.